Continest,coast,ocean dynamics of regionalism in eastern Asia - International Seminar on Multidisciplinary Discourse (2004 : Bangi, Selangor); Ooi, Kee Beng; Ding, Choo Ming; Universiti Kebangsaan Malaysia. Institut Alam dan Tamadun Melayu; Institute of Southeast Asian Studies (Bangi, Selangor Darul Ehsan, Malaysia : Institute Of Southeast Asian Studies, 2007)
32